Protective Effects of Red Spinach (Amaranthus tricolor L.) Ethanolic Extract on Tracheal Histopathology in Cigarette Smoke-Exposed Wistar Rats - Setiawan, Haris; Agrisukma, Salsabilla Ari Sekar; Putra, Ichsan Luqmana Indra (Jurnal Sain Veteriner, 2026)
Cigarette smoke generates free radicals that can cause various respiratory disorders. Red spinach (Amaranthus tricolor L.) is a plant rich in antioxidants, which may help neutralize free radicals produced by cigarette smoke exposure. This study aimed to evaluate the protective effects of red spinach ethanol extract on the trachea of Wistar rats exposed to cigarette smoke. Twenty-four male Wistar rats were randomly assigned to four groups: K (distilled water), KN (cigarette smoke exposure), P1 (cigarette smoke exposure with 200 mg/kg BW extract), and P2 (cigarette smoke exposure with 400 mg/kg BW extract). Treatments were administered daily for 21 consecutive days. On day 22, the rats were euthanized, and their tracheas were collected for histological analysis. The tracheal tissues were processed using the paraffin embedding method and stained with hematoxylin and eosin. The evaluated parameters included epithelial cell height, tracheal lumen diameter, and goblet cell number. Data were analyzed using one-way ANOVA followed by Duncan’s post hoc test, with significance set at p < 0.05. Results demonstrated that exposure to cigarette smoke (KN group) significantly disrupted the tracheal histological structure (p < 0.05). However, administration of 400 mg/kg BW red spinach ethanol extract (P2 group) exhibited a protective effect by preserving epithelial cell height, lumen diameter, and goblet cell number comparable to those of the control group (K). In conclusion, red spinach ethanol extract at a dose of 400 mg/kg BW effectively protects the tracheal structure of Wistar rats against cigarette smoke-induced damage by maintaining epithelial cell height, lumen diameter, and goblet cell number at near-normal levels.